A high-volumetric-capacity and high-areal-capacity ZnCo2O4 anode for Li-ion batteries enabled by a robust biopolymer binder. Issue 40 (1st October 2018) - Liu, Jie; Xuan, Yuxue; Galpaya, Dilini G. D.; Gu, Yuanxiang; Lin, Zhan; Zhang, Shanqing; Yan, Cheng; Feng, Shouhua; Wang, Lei
Abstract : A high-loading ZnCo2 O4 anode has been achieved via in situ formation of a robust network between the guar gum binder and micro-ZnCo2 O4 . Abstract : Constructing high-areal-capacity anodes with high loading for Li-ion batteries is still an enormous challenge, due to the drastic volume change of large-capacity anode materials during cycling. The conventional PVDF binder system fails to withstand the degradation of high-loading electrodes. Therefore, advanced binders are urgently required. Herein, for the first time, the guar gum (GG) biopolymer has been exploited as a robust binder for micro-sized ZnCo2 O4 (ZCO) anode materials. Because of its robust mechanical properties and strong interactions with ZCO, the cycling stability of the ZCO anode has been significantly improved with a capacity of 412 mA h g −1 after 600 cycles at 1200 mA g −1 . More importantly, the ZCO can act as a "crosslinking agent" to in situ form a robust network with GG, which efficiently maintains the electrode structure stability. Hence, a ZCO anode with an ultrahigh loading of 6.73 mg cm −2 can be achieved and deliver a high areal capacity of 5.6 mA h cm −2 . Simultaneously, benefiting from the high tap density of micro-ZCO, the ZCO anode gives a high volumetric capacity of 1179 mA h cm −3 . This study will make a significant contribution to accelerating the progress of designing high-areal-capacity anodes.